Developing a Bespoke Training Programme for Staff in a Psychiatric Intensive Care Unit: The Roxeth Ward Experience - Mehtab Ghazi Rahman; Aquino Lieu; Alexandra Constantinescu (BJPsych Open)
Aims: Psychiatric Intensive Care Units (PICUs) present a unique and challenging environment for staff, requiring specialised knowledge and skills to manage complex clinical presentations and ensure patient safety. Currently, there is a gap in readily available, comprehensive training programmes specifically tailored for PICU staff. This project aimed to develop and evaluate a bespoke training programme for staff at Roxeth Ward PICU, addressing this gap and focusing on key clinical and operational challenges pertinent to the PICU setting. The programme sought to enhance staff competency, improve patient care, and create a more positive and therapeutic ward environment.